NaOH Treatment Revolutionizes Strength of Fiber Composites Globally: Perlakuan NaOH Merevolusi Kekuatan Komposit Serat Secara Global - Pamungkas, Wahyu Aji; Widodo, Edi (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates Sansivera fiber-reinforced composite materials treated with 15% NaOH alkaline liquid for different durations using the hand lay-up method. The aim is to determine the optimal treatment duration that enhances the tensile properties of these composites. Results indicate that longer NaOH treatment periods positively impact tensile strength, with the best outcomes observed at 15% treatment for 8 hours. These findings contribute to improving the mechanical performance of Sansivera fiber composites for various industrial applications. Highlight: Sansivera composites strengthen with 15% NaOH for 8 hours. Hand lay-up method enhances industrial applicability. Optimal treatment duration for Sansivera fibers is highlighted. Keyword: Sansivera fiber composites, NaOH alkaline treatment, Tensile strength enhancement, Hand lay-up method, Industrial applications